Indirect cholecystoduodenal fistula via hepatoduodenal ligament secondary to gangrenous cholecystitis: a case report - Yasunari Fukuda; Toshiya Michiura; Daisaku Ito; Tomohiro Takahashi; Shinji Tokuyama; Hiromu Morishita; Junya Nuta; Yasuaki Miyazaki; Nobuyasu Hayashi; Kazuo Yamabe (Surgical Case Reports)
Abstract Background Cholecystoduodenal fistula is an infrequent complication of gallbladder diseases. In the majority of cases, the fistula is formed by direct communication between the gallbladder and duodenum due to gallstone impaction in the gallbladder neck. We herein report a rare case of indirect cholecystoduodenal fistula via the hepatoduodenal ligament secondary to gangrenous cholecystitis. Case presentation An 80-year-old woman suspected of having emphysematous cholecystitis by a previous doctor was referred to our hospital for urgent surgery. The initial diagnosis based on additional examinations was gangrenous cholecystitis penetrating the hepatoduodenal ligament. Since she did not complain of signs of peritonitis and was taking an anticoagulant medicine, we avoided surgery and selected percutaneous gallbladder drainage (PTGBD) instead. Contrast imaging of the PTGBD tube and upper endoscopy identified the indirect cholecystoduodenal fistula via the hepatoduodenal ligament. Despite repeated attempts at endoscopic fistula closure using clips, the fistula did not close successfully. We therefore performed laparoscopic cholecystectomy and fistula closure. The postoperative clinical course was uneventful, and she left the hospital on postoperative day 15. The resected gallbladder contained small black stones, and a histological examination revealed gangrenous cholecystitis with no malignant signatures. Conclusion We encountered a rare case of indirect cholecystoduodenal fistula via the hepatoduodenal ligament secondary to gangrenous cholecystitis that was successfully treated by laparoscopic cholecystectomy and fistula closure. It is important to recognize the possible formation of indirect cholecystoduodenal fistula in cases of gangrenous cholecystitis penetrating the hepatoduodenal ligament.